Culture as Enabler for SDGs: Learning from Jesus of Nazareth's Vision/Mission - Dagmang, Ferdinand D (Archīum Ateneo, 2021)
The UN document; Transforming Our World; affirms the enabling role of culture in its goal of transforming the world. While the UN assumes the necessity to interface with traditions; it does not take the time to articulate culture's ambivalence. This article insists that proponents of the Sustainable Development Goals (SDG) should be mindful of culture's enabling and disabling tendencies. It thus maintains that every action plan for the SDG will profit from the tradition-transforming ways of Jesus of Nazareth i) who challenged many religio-cultural traditions of his time; ii) who espoused a ministry of empowerment of the poor; iii) who was portrayed by the evangelists as the real bringer of Good News and shalom against the claim of the global powers. This paper further discusses Jesus' vision of the Kingdom of God as the guide of today's Basic Ecclesial Communities (BEC); the spearhead of a religious culture that enables the poor in their pursuit of prosperity and fulfilment. The discussion on the BEC serves to focus on the implications of Jesus' vision/ mission for sustainable prosperity and fulfilment of peoples as targets of the SDGs. Thus; this article may also be considered to articulate the need for another SDG target: the transformation of cultures.